2017
DOI: 10.1016/j.clp.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Methods That Promote Human Milk Feeding of Preterm Infants

Abstract: SYNOPSIS Best practices that translate the evidence for high dose HM feeding for preterm infants during the NICU hospitalization have been described in multiple studies but their implementation has been compromised largely due to economic and ideologic concerns. Although the rates of “any” HM feeding have increased over the last decade, efforts to help mothers maintain human milk provision through to NICU discharge have remained problematic throughout the world. Special emphasis should be placed on prioritizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
129
0
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(146 citation statements)
references
References 83 publications
(120 reference statements)
1
129
0
16
Order By: Relevance
“…Despite this widely available “friendly environment,” the great variability in BMF rates at discharge in our study suggests that an in‐depth approach to better understand the complexity of BMF at discharge in VP population is important. Indeed, supporting mothers to provide their own milk during the whole NICU stay implies a change in culture, potentially achieved with the BFHI accreditation, rather than just having protocols and using donor milk …”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Despite this widely available “friendly environment,” the great variability in BMF rates at discharge in our study suggests that an in‐depth approach to better understand the complexity of BMF at discharge in VP population is important. Indeed, supporting mothers to provide their own milk during the whole NICU stay implies a change in culture, potentially achieved with the BFHI accreditation, rather than just having protocols and using donor milk …”
Section: Resultssupporting
confidence: 75%
“…They may change their pre‐delivery wishes for human milk feeding during the course of hospitalisation . In EPIPAGE‐2, policies supporting BMF maintenance and available for the study were associated with higher rates of BMF at discharge, although we were not able to explore difficulties of breast pump dependence, maternal stress and fatigue, insufficient social support, and inconsistent advice in NICUs, already described as having a negative impact on maintaining lactation. These policies may help defining strategies at unit level to support BMF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting BMF is a complex process, which is intricate to split into several policies, but has to be analysed as a whole (Meier et al, ; Rollins et al, ; Spatz, ). Multifactorial determinants are involved in BMF rate, particularly societal attitudes (Rollins et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the additional 88 ml of mother's own milk supply following domperidone treatment may have a clinically meaningful impact on preterm health and development. Further, higher milk supply in the postpartum period is associated with improved long‐term breastfeeding outcomes . A recent randomised study by O'Connor et al demonstrated no difference in neurodevelopmental outcomes of very preterm infants fed supplemental donor human milk compared with preterm formula, highlighting the critical importance of strategies for enhancing mother's own milk production.…”
Section: Discussionmentioning
confidence: 99%